MPRIP::PDGFRB Fusion Gene: A Rare Case Report of Adult Myeloid/Lymphoid Neoplasm With Eosinophilia and Tyrosine Kinase Gene Fusions - Taksin Ukkahad; Tanapun Thamgrang (Case Reports in Hematology)
Myeloid/lymphoid neoplasms with eosinophilia and tyrosine kinase gene fusions (MLN-TK) represent rare hematological malignancies driven by pathological fusion genes involving tyrosine kinase genes. Among these, rearrangements of the PDGFRB gene, particularly the ETV6::PDGFRB rearrangement, are frequently observed as pathogenic mutations. Conversely, instances of the MPRIP::PDGFRB fusion gene are rarely documented. In this case report, we present a 32-year-old previously healthy Thai male who presented to the hospital with constitutional symptoms and marked splenomegaly. His complete blood count revealed mild anemia, marked leukocytosis with hypereosinophilia, and mild thrombocytopenia. A bone marrow study showed hypercellular marrow with granulocytic hyperplasia extensively involved with eosinophils, without morphological evidence of blasts. Conventional cytogenetics identified a t (5; 17) (q33; p13). Further targeted RNA analysis using next-generation sequencing (NGS) detected a fusion gene involving MPRIP::PDGFRB. The patient was diagnosed with myeloid/lymphoid neoplasms with eosinophilia and MPRIP::PDGFRB rearrangement in the chronic-phase disease and was initiated on oral imatinib at a daily dose of 100 mg. One month after initiating the treatment, the patient achieved a hematological response consistent with complete response (CR) criteria. Imatinib therapy has been well-tolerated without reported adverse events, and a 1-year molecular assessment confirmed the achievement of complete molecular response (CMR).